Visual communication : integrating media, art and science - Williams, Rick.; Newton, Julianne Hickerson, 1949- (New York : Lawrence Erlbaum Associates, 2007)
"Visual Communication advances a new understanding of how nonconscious visual knowing drives thinking and behavior before and beyond reason. By engaging readers in intuitive intelligences, Visual Communication cultivates visual and media literacies that are essential to negotiating 21st century cultures with the highest levels of intelligence and grace. Innovative in its field, it provides a solid overview of the most advanced thinking and research about visual communication, teaching readers how to balance rational and intuitive ways of knowing to enhance their understanding of media and to improve their lives and work." "This book has been developed for use across multiple disciplines that recognize visual and media literacy as core to communication, understanding, and behavior. A comprehensive text for studies in communication and the arts, the book is a critical visual resource in such disciplines as anthropology, sociology, psychology, literature, and education. The beautifully illustrated text explains complex theories in media, art, and science in simple and direct ways to facilitate application through a progression of creative exercises. Students in all disciplines will benefit intellectually and personally. Readers will enjoy working through Visual Communication as a source of fundamental ideas and practices that are central to their daily lives."--BOOK JACKET.
Includes bibliographical references (p. 425-436) and indexes.
boek
Keywords: Visual communication